The Need for Psychedelic-Assisted Therapy in the Black Community and the Burdens of Its Provision - Smith, Darron T.; Faber, Sonya C.; Buchanan, NiCole T.; Foster, Dale; Green, Lilith (Frontiers in Psychiatry, 2022)
Psychedelic medicine is an emerging field of research, clinical and spiritual practice that examines substances classified as entheogens, hallucinogens on the human mind, body, and spirit. 3,4-methylenedioxymethamphetamine (MDMA) is a particular substance currently in phase-3 FDA clinical trials in the United States (US) and Canada to treat the symptoms of posttraumatic stress disorder (PTSD) by reducing fear-driven stimuli that contribute to trauma and anxiety symptoms. In 2017, the FDA designated MDMA as a “breakthrough therapy,” signaling that it has advantages in safety, efficacy, and compliance over available medication for the treatment of PTSD-related stress and anxiety symptoms. In the US and Canada, historical and contemporary racial experiences are frequently experienced by Black people as persistent macro-and micro insults that trigger fear response and contribute to chronically elevated cortisol levels, similar to levels seen among those diagnosed with an anxiety disorder. This paper will explore why psychedelic assisted-therapy and psychedelic medicines are specifically needed in the Black community to address the pain of every-day, white-imposed, negative, race-based experiences and promote healing and thriving among Black, Indigenous and other People of Color (BIPOC). The author(s) discuss why psychedelic assisted psychotherapy outside of a culturally-competent provider framework is unethical, while also emphasizing the importance of psychedelic research organizations to recruit and retain BIPOC populations in research and clinical training.